Ethics and laboratory animals - KOSTOMITSOPOULOS (Ν. ΚΩΣΤΟΜΗΤΣΟΠΟΥΛΟΣ), N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Despite all the benefits, the use of animals in biomedical research was, and still is, a subject of debate with respect to its true usefulness. The sensitivity of the community and the interest of scientists working in the field of laboratory animal science and welfare have clearly demonstrated that the use of animals in biomedical research must be conducted under specific scientific, legal and ethical rules. The ethical justification of a research project starts from the initial designing phase of the project until the completion of the study and the review of the obtained results. Main considerations of an ethical documentation are: the precise definition of the goals of the project and the existing probabilities for its success, the selection of the appropriate animal model, the implementation of the 3Rs' concept for replacement, reduction and refinement, a cost/benefit analysis on the expected benefits for science and society with direct consideration to the harm created to animals, a pilot study and a systematic review of previously published animal research on the topic, the availability of the appropriate facilities, equipment and expertise to guarantee high standards of animal accommodation, husbandry, care and use. The ethical documentation of a project by scientists themselves involves team work and a sustainable rather than a one-off procedure. The ethical justification of the laboratory animal research protocols reflects the interest and the responsibility of scientists for reduction and refinement of animal experimentation. This process built a trust relationship between scientists and the society.